The Emerging Clinical Application of m6A RNA Modification in Inflammatory Bowel Disease and Its Associated Colorectal Cancer - Xu X (Dove Medical Press, 2021)
Xinwei Xu,1,* Jintu Huang,2,* Dickson Kofi Wiredu Ocansey,1,3 Yuxuan Xia,1 Zihan Zhao,1 Zhiwei Xu,1 Yongmin Yan,1 Xu Zhang,1 Fei Mao1 1Department of Clinical Laboratory Diagnostics, Key Laboratory of Medical Science and Laboratory Medicine of Jiangsu Province, School of Medicine, Jiangsu University, Zhenjiang, Jiangsu, 212013, People’s Republic of China; 2Clinical Laboratory Department, The People’s Hospital of Danyang, Affiliated Danyang Hospital of Nantong University, Zhenjiang, Jiangsu, 212300, People’s Republic of China; 3Department of Clinical Laboratory Diagnostics, Directorate of University Health Services, University of Cape Coast, Cape Coast, Ghana*These authors contributed equally to this workCorrespondence: Fei MaoKey Laboratory of Medical Science and Laboratory Medicine of Jiangsu Province, School of Medicine, Jiangsu University, Zhenjiang, 212013, Jiangsu, People’s Republic of ChinaTel/Fax +86 511 8503 8215Email maofei2003@ujs.edu.cnAbstract: Methylation, first proposed in DNAs, but later found in RNAs, serves as one of the most widespread epigenetic modifications in eukaryotes, where N6-methyladenosine (m6A) modification has been found to play an important role in a variety of cancers including colorectal cancer (CRC). Under the action of various enzymes and proteins, the regulatory role of m6A in RNAs and immune cells has also been gradually realized. This paper reviews the general biogenesis and effects of m6A, and its emerging crucial role in intestinal mucosal immunity via the regulation of RNAs and immune cells, and thus closely related to the occurrence and development of inflammatory bowel disease (IBD) and CRC. m6A-related genes and regulatory factors are expected to be potential predictive markers and therapeutic targets.Keywords: N6-methyladenosine, inflammatory bowel disease, colorectal cancer, non-coding RNA, intestinal mucosal immunity